2019
DOI: 10.3390/ijms20246309
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress Induces Cell Cycle Arrest at the G2/M Phase Through eIF2α Phosphorylation and GADD45α

Abstract: Endoplasmic reticulum (ER) stress is known to influence various cellular functions, including cell cycle progression. Although it is well known how ER stress inhibits cell cycle progression at the G1 phase, the molecular mechanism underlying how ER stress induces G2/M cell cycle arrest remains largely unknown. In this study, we found that ER stress and subsequent induction of the UPR led to cell cycle arrest at the G2/M phase by reducing the amount of cyclin B1. Pharmacological inhibition of the IRE1α or ATF6α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 45 publications
4
48
2
Order By: Relevance
“…Transcriptional upregulation of p21, in this case, could be a consequence of another, distinct from p53-dependent, mechanism engaging GCN2-eIF2α-p21 pathway [40]. In addition, growth arrest may result from ER stress-induced regulation of G2/M transition through the eIF2α signaling pathway [41]. This finds confirmation in observations on DNA damage-mediated tubular endoplasmic reticulum extension, promoting apoptosis by the facilitation of ER-mitochondria signaling [42].…”
Section: Discussionsupporting
confidence: 52%
“…Transcriptional upregulation of p21, in this case, could be a consequence of another, distinct from p53-dependent, mechanism engaging GCN2-eIF2α-p21 pathway [40]. In addition, growth arrest may result from ER stress-induced regulation of G2/M transition through the eIF2α signaling pathway [41]. This finds confirmation in observations on DNA damage-mediated tubular endoplasmic reticulum extension, promoting apoptosis by the facilitation of ER-mitochondria signaling [42].…”
Section: Discussionsupporting
confidence: 52%
“…Growing evidence has suggested that early ER stress can protect cells against injuries, however, when ER was not able to deal with those stimuli, ER stress may induce apoptosis pathway [13,14]. In addition, ER stress affects cell growth by regulating cell cycle and differentiation process [15][16][17]. Such roles of ER stress in cell cycle distribution and apoptosis regulation make it become an important cellular response during exposure to some anti-cancer medicine.…”
mentioning
confidence: 99%
“…In the context of 661W proliferation under initial conditions in the study described here, on the other hand, DNA damage can induce cells to interrupt cell division [ 152 ]. Cell cycle arrest is a pro-survival feature of the earlier stages of ER stress, which is assumed to be coordinated with selective control of protein translation and DNA synthesis [ 153 ]. Ddit3 expression is associated with cell cycle arrest, in response to oxidative stress and DNA damage, and also downstream from PERK activation as an element of ER stress [ 154 , 155 ].…”
Section: Discussionmentioning
confidence: 99%